Analisys of Farmers Perceptions of Alsintan Service Business (UPJA) In UPJA Tirtosari, Gunung Kidul, D.I Yogyakarta - Irwanto; Adi Prayoga; Kemal Mahfud; Temy Indrayanti (Politeknik Pembangunan Pertanian Bogor, 2023)
This study aims to determine the level of farmers' perceptions of Alsintan Service Enterprises (UPJA) and the factors that influence farmers' perceptions of UPJA. The research was conducted using survey techniques, descriptive analysis and inferential statistics. The research location was determined purposively, namely Gunungkidul Regency, Yogyakarta Special Region. The UPJA sample was determined purposively, namely UPJA Tirtosari. The sample of farmers was determined purposively, namely UPJA customer farmers as many as 30 respondents, both members of the UPJA group and not members of the UPJA group. Analysis of the level of farmers' perceptions of UPJA statistically quantitative descriptive using a Likert scale with a score of 1 - 5, and the factors that influence farmers' perceptions using multiple linear regression analysis with the Ordinary Least Square (OLS) method. The results showed that farmers' perceptions of UPJA with a score of 4.31 were in the very good category. Perception-forming factors, namely length of formal education, age, farming experience, land area, access to information, the role of extension workers and the role of farmer groups simultaneously influence farmers' perceptions of UPJA significantly. The factor of the role of farmer groups influences farmers' perceptions of UPJA very significantly.